Exploring Attitudes towards a Randomised Controlled Trial of Venous access Devices – a Nested Pre-trial Qualitative Study. Issue 5 (September 2015) - Ritchie, Moira; Kelly, Linda J.; Moss, Jonathan; Paul, James; Shaw, Rebecca
Purpose: This pre-trial qualitative research study was carried out to explore patient and clinical staff attitudes to central venous access devices (CVADs). In addition, views about participation in a randomised controlled trial (RCT) were explored with the aim of maximising recruitment to an imminent RCT of three CVADs. Methods: Three patient focus groups (each comprising three patients) and 23 interviews with clinical staff were conducted. Interviews and focus group discussions were digitally recorded, transcribed verbatim, anonymised, uploaded to the QSR NVivo10 qualitative software programme and thematically analysed. Results: Analysis of focus group interviews revealed the added challenges that a CVAD poses to patients with cancer. Four key themes emerged: continuity of daily life, pain and discomfort, stigma (a mark of disgrace associated with certain conditions) and self-preservation. The findings show the impact of a CVAD on patients' ability to manage their condition. Clinical staff interviews highlighted several potential barriers to recruitment; a lack of equipoise (genuine clinical uncertainty as to which intervention is the most beneficial), concerns about the logistics of device insertion and a perceived requirement for education and training. Conclusions: This qualitative study raises awareness of key areas of concern to patients who need a CVAD for chemotherapy delivery. It was identified that there is a need for clearer patient information around CVADs. Additionally it allows investigators to identify barriers to recruitment in a timely manner in order to minimise the potential for conflict between the roles of carer and researcher and consequently, maximise recruitment to the RCT.